Comparison of the Effects of Reality Therapy and Cognitive Behavioral Therapy on the Resilience and Adjustment of Family Caregivers of Children with Autism - Hossein Shiroudi, Haniyeh; Pirkhaefi, Alireza (Applied Family Therapy Journal (AFTJ), 2026)
Objective: The present study aimed to compare the effectiveness of reality therapy and cognitive behavioral therapy on resilience and adjustment among family caregivers of children with autism spectrum disorder.Methods and Materials: This study was conducted using a quasi-experimental design with a pretest–posttest format and a control group. The statistical population included all family caregivers of children with autism spectrum disorder who were members of the Tehran branch of the Iran Autism Association. A total of 45 participants were selected through purposive sampling and assigned into three groups, including a reality therapy group (n = 15), a cognitive behavioral therapy group (n = 15), and a control group (n = 15). The experimental groups participated in eight weekly group intervention sessions, while the control group received no intervention. Data were collected using the Connor–Davidson Resilience Scale and the Sinha and Singh Adjustment Questionnaire. The obtained data were analyzed using repeated measures multivariate analysis of variance in IBM SPSS Statistics.Findings: The results demonstrated that both reality therapy and cognitive behavioral therapy significantly improved resilience and adjustment among family caregivers of children with autism spectrum disorder compared with the control group. The repeated measures analysis of variance indicated significant effects of time and the interaction between time and group for resilience and adjustment (p < 0.001). Bonferroni post hoc comparisons further revealed significant differences between each experimental group and the control group in posttest scores. However, no statistically significant difference was observed between the reality therapy and cognitive behavioral therapy groups regarding resilience and adjustment outcomes (p > 0.05), indicating that both interventions were equally effective.Conclusion: The findings suggest that both reality therapy and cognitive behavioral therapy are effective interventions for improving resilience and adjustment among family caregivers of children with autism spectrum disorder.